Physical intelligence of UiTM Sport Science undergraduates - Wee, Eng Hoe; Tan, Chee Hian (2004)
The purpose of this investigation is to determine the physical intelligence among the Sports Science undergraduates who are currently enrolled at the Faculty of Sports Science and Recreation, Universiti Teknologi MARA Shah Alam campus and branch campuses (Arau and Kuching campuses). The model of this study is based on Denis Postle’s (The Mind Gymnasium,1989) Model of multiple intelligence. Denis Postle’s model includes four types of intelligence : 1) Emotional Intelligence, 2) Intuitive Intelligence, 3) Physical Intelligence and 4) Intellectual Intelligence. This study only examine Physical Intelligence. Further, this study adopted 5 dimensions of the 6 dimensions of Postle’s Physical Intelligence which were fitness and health, enjoyment of physical activities, pride in manual skills and dexterity, sensible and balanced diet and love of the outdoors. A total of 215 Sport Science undergraduates enrolling in the Diploma and Degree courses were examined. Data were collected through a questionnaire formulated by the researchers. Results indicated that there was no significant difference in physical intelligence among undergraduates from different age groups. However, when undergraduates from different programmes were compared, significant difference was found in the ‘love of outdoor’ dimension. Multiple comparisons results showed that significant difference was between Diploma and Bachelor of Sport Science undergraduates with Diploma undergraduates love the outdoor more than Bachelor of Sport Science undergraduates.